The Optimal Location for The Development of Agricultural Production Center Area of Rembang Regency - Pigawati, Bitta; Suryani, Tia Adelia; Barbarossa, Ghiffari (Universitas Negeri Semarang, 2022)
Abstract. Disproportionate regional spatial growth can encourage regional disparities between villages and cities and problems for the sustainability of regional development. Rembang Regency has growth characteristics that are concentrated at several points in its urban area. This pattern of growth creates a problem of regional disparity. To overcome this problem, it is necessary to add new regional growth centers. These new regional growth centers are expected to evenly distribute spatial growth. The center of regional growth in accordance with the characteristics of Rembang Regency is the center of agricultural production. This study aims to determine the optimal location for the development of the agricultural production centers as the center of regional growth. Using a spatial approach with remote sensing images as the main data. The analytical technique used is spectral transformation and multicriteria. The results showed that the most optimal locations for the development of agricultural production centers were Sale District (2,634.01 ha), Gunem District (2,198.95 ha) and Kragan District (2,171.72 ha). Sulang District is also a potential location for the development of agricultural production centers because the total area of the optimal location covers 8 – 10% of the total area of Rembang Regency. The findings of the study on the optimal location for the development of agricultural production centers are recommended as a strategic area for regional development to function as a growth center for Rembang Regency as an effort to overcome disproportionate spatial growth.